Direct medical costs of severe asthma in two colombian reference centers (2020)
Objectives: Severe asthma, although infrequent, generates an important clinical and economic burden in both patients and healthcare system. We aimed to describe demographic and clinical characteristics, exacerbations, healthcare resource utilization (HRU), and annual direct medical costs in a severe asthma patient cohort in Colombia. Methods: Cost ofillness study from payer perspective. Patients with clinicianconfirmed severe asthma diagnosis (GINA criteria) from two specialized reference centers between January 2014 and August 2018 were included. The last year within this period under GINA step 4/5 therapy was observed for each patient. Clinical information was extracted from medical records, and HRU from hospital invoices and public price lists. Results: 147 patients were included, 59% female. Mean (6SD) age and time with asthma diagnosis was 46615 and 21617 years, respectively. Most frequent comorbidities were allergic rhinitis (70%), conjunctivitis (27%) and hypertension (19%). Most common sensitization cause was house dust mite (61%). Median baseline blood eosinophil count was 260 cells/ml (range 10-4,040), mean total IgE serum level was 69761,893 IU/ml. The mean annual frequency of HRU was 5.064.0 for laboratory tests, 4.161.2 for medical visits, 1.061.5 for emergency visits, 0.360.7 for hospitalizations, and 0.160.3 for ICU. Omalizumab was prescribed in 42.2% of patients, with a mean among users of 30.2620.3 vials per year. Mean annual direct cost for outpatient care was 4,743.666,331.1 USD (range 256.7-31,286.1) (1 USD=2,956.4 COP); medications were responsible for 98% of costs. Data from 55 hospitalizations was obtained, 4 in ICU. Mean stay and cost per episode were 6.564.9 days and 1,010.561,379.9 USD in general ward, and 14.164.1 days and 3768.963748.2 USD in ICU. Conclusions: Severe asthma is a costly disease for the Colombian health system. Most of the direct outpatient medical costs in this cohort were caused by pharmacological therapy, particularly omalizumab. Funding: GSK (PRJ2813)